2020
DOI: 10.1007/s11104-020-04609-x
|View full text |Cite
|
Sign up to set email alerts
|

Native and non-native trees can find compatible mycorrhizal partners in each other’s dominated areas

Abstract: Aims Biological invasions have historically been addressed mostly from an aboveground perspective, so little is known about the impacts of belowground invasions. We studied the impact of belowground invasions on growth of native tree species and test the possibility of novel interactions between native and non-native hosts and native and non-native belowground symbionts. Methods We combined field and growth chamber studies. With a growth chamber bioassay we compared growth and root colonization percentage of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…Here, we show, for the first time, that the most invasive pine species associate more frequently with the most invasive EMF species. Our results are consistent with recent findings showing that pine species that are more invasive depend more upon their EMF (Moyano et al, 2020), a phenomenon that contradicts the idealweed hypothesis, which posits that invasive plant species depend less on mutualistic interactions (van der Putten et al, 2007;Moyano et al, 2020Moyano et al, , 2021. Pinaceae species seem to be interesting exceptions to this idea (Dickie et al, 2010;Nuñez & Dickie, 2014;Bogar et al, 2015;Moyano et al, 2020), being more successful when their EMF mutualists are also invasive.…”
Section: Forumsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we show, for the first time, that the most invasive pine species associate more frequently with the most invasive EMF species. Our results are consistent with recent findings showing that pine species that are more invasive depend more upon their EMF (Moyano et al, 2020), a phenomenon that contradicts the idealweed hypothesis, which posits that invasive plant species depend less on mutualistic interactions (van der Putten et al, 2007;Moyano et al, 2020Moyano et al, , 2021. Pinaceae species seem to be interesting exceptions to this idea (Dickie et al, 2010;Nuñez & Dickie, 2014;Bogar et al, 2015;Moyano et al, 2020), being more successful when their EMF mutualists are also invasive.…”
Section: Forumsupporting
confidence: 91%
“…While EMF at the invasion front are generally better at dispersing, forming a long-lasting spore bank, and exploring longer distances for roots, EMF in mature pine invasions require higher root density and have shortdistance exploration types (Ashkannejhad & Horton, 2006;Peay et al, 2011). Even when there is increasing evidence about this invasion pattern (Nuñez et al, 2009;Dickie et al, 2010;Hayward et al, 2015a;Urcelay et al, 2017;Policelli et al, 2020), it is still unclear whether pine invasiveness is related to the invasion ecology of their obligate root symbionts.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the ECM fungi consumed by S. rubecula and P. tarnii, such as Cystangium nothofagi and species of Cortinarius, Descolea, and Inocybe, are important ECM fungi that colonize the roots of seedlings and saplings of several species of Nothofagaceae. [82][83][84] The results of our viability tests show that nearly half of the fungal spores in fecal samples are able to survive intact after passage through the digestive systems of the birds. It is important to note that not all structurally intact spores are capable of germinating and that our estimates cannot assess the germination rate itself, only the structural integrity of the spores.…”
Section: Discussionmentioning
confidence: 91%
“…The result is correlated with losses in plant community diversity (Nuñez et al 2017). In contrast, it has been demonstrated in a growth chamber study that native Nothofagus (Blume) trees and non-native pine trees grown in pine-invaded soils and non-invaded soils grew equally well in both soils in terms of biomass and ectomycorrhizal root colonisation, suggesting the presence of each host (and their mutualists) did not necessarily hinder the other (Policelli et al 2020). The implications of such interactions on future plant communities and the subsequent PSF remains relatively unknown, particularly when designing invasive species management plans (Dickie et al 2022).…”
Section: Microbial and Soil Organism Interactionsmentioning
confidence: 94%
“…In line with this, studies have shown that Pinus spp. L. co-invade with beneficial ectomycorrhizal fungi from their native range (Dickie et al 2010;Policelli et al 2020;Sapsford et al 2022). As the density of the co-invading pines and ectomycorrhizae increases, saprotrophic diversity decreases drastically, suggesting this loss is due to competitive exclusion of saprotrophs by ectomycorrhizae (Sapsford et al 2022).…”
Section: Microbial and Soil Organism Interactionsmentioning
confidence: 99%